Characterization of an Escherichia coli plasmid encoding for synthesis of heat-labile toxin: molecular cloning of the toxin determinant. - So, M (1978)
P307 is a plasmid isolated from a strain of Escherichia coli that was responsible for an outbreak of diarrheal disease in piglets. This 60 X 10(6)-dalton plasmid was subsequently shown to encode for the synthesis of a heat-labile toxin (LT). Using recombinant DNA technology, we isolated a 7.8 X 10(6)-dalton DNA fragment that contains the LT gene(s). This fragment was generated using an EcoRI partial digestion of P307 DNA, and the fragment was joined to a small multicopy plasmid, RSF2124. E. coli strains harboring the chimeric plasmid produced greater amounts of LT than did the same strains containing P307. The LT genes were also isolated on a 5.8 X 10(6)-dalton DNA fragment made by BamHI digestion, and we identified an EcoRI recognition sequence that is located in a position essential for LT synthesis.